Conference Review: European Textile Forum 2016 - Heather Hopkins (EXARC, 2017)
The annual European Textile Forum took place from 7-13 November 2016. This year the focus was ‘mistakes’, the unintended consequences in textile manufacture or preservation that reveal more about the artefact, the techniques used and its makers than a ‘perfect’ piece could do. The programme was rich in practical experiments, making use of the conference and laboratory facilities. There were lectures, workshops, roundtable discussions and a day’s visit to the Römisch-Germanisches Zentralmuseum (RGZM) in Mainz. The forum is a place where academics, professionals, re-enactors, skilled amateurs and novices can meet to present new ideas and findings, compare notes, advise, reflect and learn new skills. The European Textile Forum is a proving ground for new theories in a friendly environment, organised by Katrin Kania and Sabine Ringenberg. Delegates could stay the length of the conference, a couple of days or use day passes to visit as they wished.